Eurom 5 : ce que l’intercompréhension romane peut apporter aux langues slaves - Labbe, Gregoire (Slavia Centralis, 2020)
In this article, we would like to present an overview of intercomprehension between languages of a same family as a linguistic and didactic field and to provide a concrete example of how it can look like, thanks to the methodology created for Eurom 5 (Bonvino et al., 2001). Our goal is to describe this methodology and show the potential advantages such an approach can represent for Slavic languages and for Slavic speakers at a time when a knowledge of English is all too often the only linguistic skill developed.